Islam and Politics in Indonesia : The Masyumi Party between Democracy and Integralism - Madinier, Remy; Desmond, Jeremy; Project Muse. (Singapore : NUS Press, 2015)
The Masyumi Party, which was active in Indonesia from 1945 to 1960, constitutes the boldest attempt to date at reconciling Islam and democracy. Masyumi proposed a vision of society and government which was not bound by a literalist application of Islamic doctrine but rather inspired by the values of Islam. It set out moderate policies which were tolerant towards other religious communities in Indonesia. Its achievements were nonetheless precarious: it was eventually outlawed in 1960. Many of its leaders then turned to integralism, a radical doctrine echoing certain characteristics of 19th-century Catholic integralism, which contributed to the advent of Muslim neo-fundamentalism in Indonesia. This book examines the Masyumi Party from its roots in early 20th-century Muslim reformism to its contemporary legacy.
Epilogue -- Archetypal Contradictions within Muslim Reformism in Indonesia: Masyumi as Inheritors and PerpetuatorsGlossary; Bibliography; Index
English translation of the author's original French work.
Description based on print version record.
Keywords: Masyumi (Organization); Masyumi (Organization) -- History; Politics and government; Political parties; Islam and state; Islam and politics; HISTORY -- Asia -- Southeast Asia; Asian history; Islam et État -- Indonesie -- Histoire -- 20e siecle; Political parties -- Indonesia -- History -- 20th century; Islam and state -- Indonesia -- History -- 20th century; Islam and politics -- Indonesia -- History -- 20th century; Indonesia; Indonesie -- Politique et gouvernement -- 1950-1966.; Indonesie -- Politique et gouvernement -- 1942-1949.; Indonesia -- Politics and government -- 1950-1966.; Indonesia -- Politics and government -- 1942-1949.; History; Electronic books